THE PORTRAYAL OF WOMEN'S SUBORDINATION IN A DYSTOPIAN NOVEL ENTITLED WITHER BY LAUREN DESTEFANO (2011) - Annisa Fauziah, - (2018)
Wither (2011) is a dystopian novel about the destruction of the world as the aftereffect of World War III. The situation worsens after a deadly virus emerges due to a failure of a genetic trial. Women in the novel are subordinated as they are mainly seen as a baby-producing machine by men so that humans will not be extinct. The study aims to analyze how the subordination of women is portrayed in the novel Wither. Applying a qualitative approach and textual analysis, this study uses Mitchell's (1966) socialist feminist theory due to the subordination of women which occurs in more than one sectors. Additionally, to untangle the portrayal of women's subordination in the novel, the study analyzes the literary elements of the novel guided by Roberts and Jacobs' (2004) elements of fiction focusing primarily on narration, character and characterization, style, diction and dialogue. The data analysis shows that women's subordination is portrayed mostly through narration and diction, and occurs in four different structures: sexuality, reproduction, production, and socialization. The subordination, however, primarily occurs in terms of sexuality. This research is expected to not only contribute to the study of women's subordination but also to increase people's awareness of different forms of subordination in the society, and that they know how to resist and act against it.